Lipase-Catalyzed Synthesis of Substituted Phenylacetamides: Hammett Analysis and Computational Study of the Enzymatic Aminolysis - Garcia Liñares, Guadalupe Eugenia (2014)
A series of hydroxy-, methoxy-, and nitrophenylacetamides was synthesized by enzyme catalysis. The 28 new products were obtained through a lipase-catalyzed two-step reaction in very good to excellent yield. In the case of nitro derivatives, a one-pot, two-step methodology allowed the desired products to be obtained in high yields. The influence of various reaction parameters in the lipase-catalyzed reactions, such as enzyme source, nucleophile (alcohol or amine)/substrate ratio, enzyme/substrate ratio, solvent and temperature were studied. It was observed that nitro-substituted phenylacetates were more reactive in the aminolysis reaction than phenylacetates substituted with a hydroxyl group. To study this substituent effect, a Hammett analysis and the determination of the ρ parameter were carried out. Moreover, a computational study was applied to the most representative systems, performing an exploration of the potential energy surface for the catalyzed and noncatalyzed aminolysis reaction for nitro- and hydroxyphenylacetates. Both analysis showed that the presence of a strongly electron-attracting group favors the activity of the enzyme, in complete agreement with the experimental results of the enzymatic catalysis.